Anti-Stunting Education Strategy in Daycare: Analysing the Role of Caregivers and Families towards Early Childhood - Nabila, Annisa Fara; Muthohar, Sofa; Nasikhin, Nasikhin; Razak, Abdul (UIN Sultan Maulana Hasanudin Banten, 2024)
The high rate of stunting in Indonesia has a negative impact on children’s health. This suggests the need for effective interventions. The purpose of this study is to determine the anti-stunting education strategy in daycare by analysing the role of caregivers and families towards early childhood. This research discusses the pattern of anti-stunting education implemented in Rumah Pelita Daycare, the role of parents and caregivers in reducing stunting, and the implications of anti-stunting education on child development. This research uses a qualitative case study method through observation, interviews, documentation. Data analysis uses the Miles and Huberman approach through the stages of reduction, data presentation, conclusion drawing. The results showed that Rumah Pelita Daycare is committed to reducing stunting rates through comprehensive efforts, namely providing nutritional intake, clean and healthy living behaviour, routine examinations, learning activities, implementing naps. Parents are also involved in parenting classes and counselling. This research provides practical and theoretical understanding of the role of caregivers and families towards early childhood in anti-stunting education.